IMPLEMENTATION OF LEARNING DIFFICULTY DIAGNOSIS PRACTICUM TO IMPROVE THE EFFECTIVENESS OF LEARNING STRATEGIES IN SCHOOLS - Nurhani Fakhita; Septika Amanda Siagian; Sri Mullatifah Hanum; Uswatun Hasanah (Jurnal Eduslamic, 2025)
The aim of this research is to examine the implementation of learning difficulty diagnosis practices in improving the effectiveness of teaching strategies in schools. This study uses a qualitative method with a descriptive approach to explore teachers' experiences in diagnosing students' learning difficulties and the implications for teaching strategies. Data were collected through interviews with teachers, classroom observations, and the analysis of documents such as lesson plans and reports on learning difficulty diagnoses. The data analysis technique used was thematic analysis with triangulation to ensure the validity and reliability of the data. The research findings show that diagnosing learning difficulties helps teachers identify barriers faced by students, both internal (such as low motivation or health issues) and external (such as family environment or unsuitable teaching methods). This diagnostic practice allows teachers to design more effective teaching strategies tailored to the individual needs of students. However, challenges such as limited resources, time, student participation, and teachers' competence in conducting diagnoses remain significant hurdles. This study recommends that teachers receive further training and adequate support in resources to enhance the effectiveness of learning difficulty diagnosis practices in schools.